ANALISIS GIZI BERMASALAH KASUS STUNTING TERHADAP ANAK USIA 1-2 TAHUN - Purba, Ivan Elisabeth; Sinaga, Taruli Rohana; Adiansyah (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Chronic malnutrition in children of growing age affects stunting cases. Based on data from the infant nutritional status survey in Indonesia in 2021, 25.5% was found in Mandailing Natal Regency at 47.7%, Deli Serdang Regency at 12.5% while in Medan city, the number of stunting cases was 19.9%. The purpose of the study was to analyze the problematic nutrition of stunting cases in children aged 1-2 years. The type of research method used in this research is qualitative with data collection carried out by interview techniques and literature studies at several health centers and hospitals in the Medan city area. The research data obtained from a total of 17 toddlers who have 1-2 years of age found there are 6 children (2.8%) toddlers who have stunting disease, risk factors that cause stunting are caused by a lack of nutrition or nutritional needs in toddlers in the womb until the growth period of 1-2 years, this will have a major impact on child growth and development.